Travel Writing, Visual Culture, and Form, 1760-1900
XIV, 248 p.
Keywords: This collection reveals the variety of literary forms and visual media through which travel records were conveyed in the long nineteenth century, bringing together a group of leading researchers from a range of disciplines to explore the relationship between travel writing, visual representation and formal innovation.